2013
DOI: 10.1530/eje-12-0955
|View full text |Cite
|
Sign up to set email alerts
|

Body weight loss reverts obesity-associated hypogonadotropic hypogonadism: a systematic review and meta-analysis

Abstract: Objective: Few randomized clinical studies have evaluated the impact of diet and physical activity on testosterone levels in obese men with conflicting results. Conversely, studies on bariatric surgery in men generally have shown an increase in testosterone levels. The aim of this study is to perform a systematic review and meta-analysis of available trials on the effect of body weight loss on sex hormones levels. Design: Meta-analysis. Methods: An extensive Medline search was performed including the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
290
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(332 citation statements)
references
References 66 publications
23
290
2
5
Order By: Relevance
“…Bariatric surgery has been extensively described to ameliorate sex hormone and SHBG levels in morbidly obese patients (9,14,15,16,17,18,19), with an effect that may exceed what is predictable on the basis of weight loss (17). In this study, we demonstrate that the increase in androgens (cFT and TT) occurs only in hypogonadal patients (TT!8 nmol/l).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Bariatric surgery has been extensively described to ameliorate sex hormone and SHBG levels in morbidly obese patients (9,14,15,16,17,18,19), with an effect that may exceed what is predictable on the basis of weight loss (17). In this study, we demonstrate that the increase in androgens (cFT and TT) occurs only in hypogonadal patients (TT!8 nmol/l).…”
Section: Discussionmentioning
confidence: 51%
“…The previous works reported that BMI (9,17) and age (18) were among the best predictors of androgen recovery after bariatric surgery. However, such cohorts of morbidly obese patients included both hypogonadal and eugonadal subjects.…”
Section: Discussionmentioning
confidence: 95%
“…It has been estimated thatMore markedly (O30%), body weight loss secondary to bariatric surgery can raise testosterone by O10 nmol/l (Grossmann 2011). This has been confirmed by a recent systematic review and meta-analysis of studies that have reported the effects of weight loss on testosterone levels (Corona et al 2013b). Non-surgical weight loss achieved a mean weight reduction (9.8%) in body weight.…”
Section: Testosterone and Insulin Resistance: A Bilateral Relationshipmentioning
confidence: 83%
“…In addition, suppression of secretion of SHBG in the liver and conversion of testosterone into estradiol in adipose tissues as a result of developing hyperinsulinism due to increase of body weight also adversely affect the sexual functions (2). In a meta-analysis it has been found that, SHBG, LH, FSH, and free and bound testosterone levels increased, and estrogen levels decreased due to weight loss in men after bariatric surgery (6). In another study, increased prolactin and decreased testosterone levels have been associated with decreases in sexual arousal (32).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity related diseases such as diabetes mellitus, chronic hypertension and respiratory diseases have been developing and distracting the quality of life (5). About 3 million people die annually due to obesity-related complications (6).…”
Section: Introductionmentioning
confidence: 99%